The crisis of South African foreign policy : diplomacy, leadership and the role of the African National Congress - Graham, Matthew (Lecturer) (International library of African studies, 2015)
"The emergence of a 'new' democratic South Africa under Nelson Mandela was regarded as a high watermark for international ideals of human rights and democracy. Much was expected of the ANC in power, particularly that it would be able to translate its ideals into a coherent foreign policy for the African continent. Yet its foreign policy since 1994 has been mired in accusations of incoherence, contradiction and failure. Here, based on extensive archival research and interviews, Matthew Graham offers new ways of interpreting South Africa's foreign policy by investigating the continuities and discontinuities of the ANC's international relations - from exile to political power. Charting the political intrigues during the country's transition from apartheid, and the subsequent influences on Presidents Mandela and Mbeki, The Crisis of South African Foreign Policy makes a vital contribution to our understanding of why post-apartheid South Africa has failed to lead Africa on the world stage."--Back cover